An Acidic Exopolysaccharide from Haloarcula hispanica ATCC33960 and Two Genes Responsible for Its Synthesis. (28th May 2017) - Lü, Yang; Lu, Hua; Wang, Shiwei; Han, Jing; Xiang, Hua; Jin, Cheng
Abstract : A 1.1 × 10 6 Da acidic exopolysaccharide (EPS) was purified from an extremely halophilic archaeon Haloarcula hispanica ATCC33960 with a production of 30 mg L −1 when grown in AS-168 medium, which mainly composed of mannose and galactose with a small amount of glucose in a molar ratio of 55.9 : 43.2 : 0.9. Two glycosyltransferase genes ( HAH_1662 and HAH_1667 ) were identified to be responsible for synthesis of the acidic EPS. Deletion of either HAH_1662 or HAH_1667 led to loss of the acidic EPS. The mutants displayed a different cell surface morphology, retarded growth in low salty environment, an increased adhesion, and swimming ability. Our results suggest that biosynthesis of the acidic EPS might act as an adaptable mechanism to protect the cells against harsh environments.